2020
DOI: 10.1016/j.jos.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Increase in medial meniscal extrusion in the weight-bearing position observed on ultrasonography correlates with lateral thrust in early-stage knee osteoarthritis

Abstract: Background: Lateral thrust is known to be risk factors for knee osteoarthritis progression. Medial meniscus extrusion is also known to be risk factors for knee osteoarthritis progression; moreover, the amount of change in medial meniscus extrusion from non-weight bearing to weight bearing is an important factor for the progression of knee osteoarthritis. This study aimed to investigate the correlation between lateral thrust and the change in medial meniscus extrusion. Methods: In total, 44 knees from 44 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Many ultrasonography studies have evaluated the state of the meniscus with or without load conditions in both healthy individuals 15 and patients with moderate or severe KOA 16 , 17 . However, to the best of our knowledge, no study has evaluated patients exhibiting Kellgren–Lawrence (K–L) grades of 0 or 1.…”
Section: Introductionmentioning
confidence: 99%
“…Many ultrasonography studies have evaluated the state of the meniscus with or without load conditions in both healthy individuals 15 and patients with moderate or severe KOA 16 , 17 . However, to the best of our knowledge, no study has evaluated patients exhibiting Kellgren–Lawrence (K–L) grades of 0 or 1.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the progression of OA, based on the findings from this study and previous reports, occurs as follows: extrusion of the MM, which is an important cause of OA, causes the medial femoral condyle to come into direct contact with the medial tibial cartilage that lacks the MM. Extrusion of the MM also induces varus alignment 25 and/or lateral thrust 26 . These changes result in cartilage defects and further enlargement of those defects.…”
Section: Discussionmentioning
confidence: 99%
“…Single-leg sensor metrics were associated with surrogate measures of varus thrust, and midthigh adduction velocity was significantly associated with peak external knee adduction moment 3 IMU b (Trigno IM Sensors, Delsys Inc) on thigh, midshank, and distal shank Knee OA a (n=26) Costello et al, 2020 [33] Positive correlation between lateral thrust and change in medial meniscus extrusion 2 IMU c (WAA-010, ATR-Promotions) placed on tibia and foot Knee OA (n=44) Ishii et al, 2020 [34] Moderate correlation found between acceleration peak in IMU frame and KAM, values from shank IMU had strongest correlation 6 IMU c (TSND151, ATR-Promotions) on pelvis, sternum, shanks, and thighs Knee OA (n=22) Iwama et al, 2021 [35] High accuracy and repeatability of foot progression angle measures, and feedback effectiveness was similar between wearable and laboratory feedback setups 7 IMU b (MTw, Xsens Technologies BV) on pelvis, thighs, shanks, and feet Healthy (n=11) Karatsidis et al, 2018 [38] Two machine learning algorithms were highly accurate (R 2 approximately 0.95) in predicting KAM using IMU input 2 IMU c (DA14583, Dialog Semiconductor) on malleoli Healthy (n=12), knee OA (n=78) Wang et al, 2020 [36] Good correlation coefficients to discriminate between different foot progression angle walking conditions 2 IMU b (MTw Awinda, Xsens Technologies BV) on feet Healthy (n=5) Wouda et al, 2021 [37] Participants were able to respond to feedback during walking and adopt target foot progression angle conditions Single IMU b (custom-made) embedded in shoe sole Healthy (n=10) Xia et al, 2020 [39] a OA: osteoarthritis.…”
Section: Findings Sensor Population Studymentioning
confidence: 99%